FACTORS AFFECTING THE INCOME OF PATCHOULI FARMERS INWEST WOYLA AND WOYLA DISTRICTS, WEST ACEH REGENCY: FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI NILAM DI KECAMATAN WOYLA BARAT DAN WOYLA KABUPATEN ACEH BARAT - Khairun Nisa; Safrika; Liston Siringo Ringo; Suwaibah Aslamiyah (ROCE : Jurnal Pertanian Terapan, 2026)
Patchouli farming is an important source of rural income in West Aceh. However, farmers still faceunstable earnings due to differences in cultivated land area, selling price, production costs, and production volume. This study aimed to analyze the factors affecting the income of patchouli farmers in the West Woyla and Woyla Districts of West Aceh Regency. A quantitative field-study approach was used. Primary data were collected through observation, interviews, and structured questionnaires involving 27 patchouli farmers selected using saturated sampling. The data were analyzed using multiple linear regression, with farmer income as the dependent variable and land area, selling price, farming cost, production volume, farming experience, and education as independent variables. The results showed that the regression model explained 87.9% of the variation in farmer income. Simultaneously, the six independent variables significantly affected income (F = 32.595; p = 0.000). Partially, land area, selling price, and production volume had positive and significant effects on income, whereas farming cost had a negative and significant effect. Farming experience and education did not significantly affect income. These findings indicate that increasing patchouli farmers' income should prioritize productive land use, production improvements, cost efficiency, and stronger price management, rather than relying solely on farming experience or formal education.